Redistributive effects of different pension structures when longevity varies by socioeconomic status in a general equilibrium setting - Miguel Sanchez-Romero; Ron Lee; Alexia Fürnkranz-Prskawetz (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Differences in life expectancy between high and low socioeconomic groups are often large and have widened recently in many countries. Such longevity gaps affect the actuarial fairness and progressivity of public pension systems. However, behavioral responses to longevity and policy complicate analysis of possible reforms. Here we consider how some pension reforms would perform in a general equilibrium OLG setting with heterogeneous longevity and ability. We evaluate redistributive effects of three Notional Defined Contribution plans and three Defined Benefit plans, calibrated on the US case. Compared to a nonredistributive plan that accounts for differences in mortality, US Social Security reduces regressivity from longevity differences, but requires group-specific life tables to achieve progressivity. Moreover, without separate life tables, despite apparent accounting gains lower income groups would suffer welfare losses and higher income groups enjoy welfare gains through indirect effects of pension systems on labor supply.
Keywords: E24; J10; J18; H55; 330; Human capital; Longevity; Inequality; Life cycle; Social Security